Move over, Rover!. - Beaumont, Karen (Orlando : Harcourt, 2006)
Although it is pouring down rain outside, Rover is warm and dry inside his doghouse, until, friends decide to join him!
Preschool
Keywords: Dogs - fiction; Animals - fiction; Rhyming - fiction